2019
DOI: 10.1016/j.socscimed.2019.112498
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine addiction as a moral problem: Barriers to e-cigarette use for smoking cessation in two working-class areas in Northern England

Abstract: Tobacco use in high-income countries correlates with socio-economic disadvantage, but although switching to electronic cigarettes could be a safer alternative, little is known about barriers to use. Drawing on eighteen months of data collection in two areas of Northern England in 2017/18 including ethnography and interviews with 59 smokers and e-cigarette users, I show that concern about continued nicotine addiction either deterred working-class smokers from switching to e-cigarettes or dictated the conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 85 publications
0
26
1
2
Order By: Relevance
“…Children's reported future smoking and vaping susceptibility were both significantly lower among those for whom e-cigarettes were perceived as devices to help adults stop smoking. In contrast to recent qualitative research, which found that poorer adults switched from tobacco cigarettes to e-cigarettes primarily because they were cheaper [52], we found that children from more affluent families were more likely to cite this as a reason for use. However, parents may communicate to their children that they are using e-cigarettes to stop smoking, without in turn communicating that this is due to issues of cost.…”
Section: Discussioncontrasting
confidence: 99%
“…Children's reported future smoking and vaping susceptibility were both significantly lower among those for whom e-cigarettes were perceived as devices to help adults stop smoking. In contrast to recent qualitative research, which found that poorer adults switched from tobacco cigarettes to e-cigarettes primarily because they were cheaper [52], we found that children from more affluent families were more likely to cite this as a reason for use. However, parents may communicate to their children that they are using e-cigarettes to stop smoking, without in turn communicating that this is due to issues of cost.…”
Section: Discussioncontrasting
confidence: 99%
“…, Hiscock et al . , Thirlway 2019b) and framing cessation messages around financial cost may be a way forward (Pisinger et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…I have suggested elsewhere that the cost of smoking, especially as it relates to the diversion of financial resources from the family to a habit negatively constructed as addiction, is an important moral consideration for working-class smokers and explains the turn to consumption of the cheapest possible tobacco as involving more than mere affordability (Thirlway 2019a). Raising the minimum price of tobacco products (Gilmore et al 2010, Hiscock et al 2012, Thirlway 2019b and framing cessation messages around financial cost may be a way forward (Pisinger et al 2011). As I have argued elsewhere, there may also be a role for switching to e-cigarettes as a way for smokers to maintain their involvement in working-class sociality and hedonism whilst reducing the risk to their health (Thirlway 2016(Thirlway , 2018.…”
Section: Discussionmentioning
confidence: 99%
“…We found no eligible studies that focussed on clearly identi able groups of other SES, suggesting there is gap in existing research in terms of qualitative research that looks across SES groups or which focuses on understanding experiences and perceptions of NCNPs in more advantaged groups. Most studies recruited from areas of the UK deemed to be either socioeconomically disadvantaged or 'working class' [30,[50][51][52][53], a term commonly used in the UK to describe lower SES groups [54]. One study [55] used the UK Townsend Deprivation Index, while three others [46][47][48] (from the same dataset) recruited participants from welfare service users in Australia.…”
Section: Study Summarymentioning
confidence: 99%
“…The authors used a friendship group approach to data collection and found that, although e-cigarettes might have some potential to contribute to smoking harm reduction and cessation among this population, the experience of stigma associated with perceived addiction and the similarity of the embodied practices of smoking meant that there was limited enthusiasm for e-cigarettes. We also identi ed another study conducted by Thirlway [54]. Based on a new dataset, but utilising a similar ethnographic methodology, Thirlway builds on the ndings of her previous study by further exploring the link between perceptions of addiction, morality and pleasure among a sample of working class smokers in Northern England.…”
Section: Strengths and Limitationsmentioning
confidence: 99%